The museum of digital things: extended reality and museum practices - Song, Zhennuo; Evans, Leighton (Frontiers in Virtual Reality, 2024)
This study presents a philosophical reconceptualisation of museums using phenomenological frameworks. It explores the role extended reality (XR) 'things' play in the museum experience and studies how their function differs from traditional objects. Existing studies highlight the technological tools, solutions and various visitor experience modalities in the museum sector. However, only a few papers focus on the theoretical aspects of using XR in museums. This empirical study adopts a qualitative research methodology, and 22 semi-structured interviews with specialists in XR design and development, museum culture, curation and museum exhibitions are conducted. The findings suggest that XR enhances museum curation and exhibition practices by providing new dimensions for interacting with museum objects. This aligns with Heidegger's 'the thing' and 'fourfold' concepts -the integration of mortals (i.e. museum visitors), earth (i.e. the activities participated in by the visitors), sky (i.e. the potentialities and ideas stimulated by the artefacts) and divinities (i.e. the visitors' emotions while interacting with the exhibits). Therefore, these new interactions, enabled by XR, can accentuate the narratives attached to and the meaning of the artefacts within the digital museum space, facilitating new understandings and relationships with history due to the digitisation of objects. Furthermore, this can potentially impact XR's use in developing multi-channel curation and multi-sensory visitor experiences in museums and cultural heritage institutions.